Saṃskāra gīta : Pahāṛī loka-sāhitya - Upamanyu, Śivakumāra; Thakur, Molu Ram; Śarmā, Vidya; Oma Prakāśa (Himācala Kalā, Saṃskrti, evam Bhāshā Akādamī, 1982)
Folk songs associated with domestic rituals in Himachal Pradesh.